The Effect of Teaching Materials for Chemical Equilibrium Based on Spiritual Values on Student Learning Outcomes in the Guided Inquiry Learning Model - Lubis, Melisa Damayanti; Darmana, Ayi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
This research was motivated by the low learning outcomes and spiritual attitudes of students. This research aims to determine the effect of chemical equilibrium teaching materials based on spiritual values on student learning outcomes and students' spiritual attitudes in the guided inquiry learning model, as well as seeing the relationship between students' spiritual attitudes and student learning outcomes. This type of research uses research methods using a sample of 60 students. The data collection methods used were (1) interview observation, (2) student spiritual questionnaire, (3) test instruments. The results of the research show that chemical equilibrium teaching materials based on spiritual values in the guided inquiry learning model have an influence on students' learning outcomes and spiritual attitudes. The research results stated that there was a difference between classes that used high school textbooks on the subject of chemical equilibrium and classes that used chemical equilibrium teaching materials based on spiritual values, namely sig (2-tailed) < 0.05 or 0.007 < 0.05. Furthermore, there is also the influence of chemical equilibrium teaching materials based on spiritual values on students' spiritual attitudes by looking at the difference between before and after being given treatment, where the sig value (2-tailed) > 0.05 or 0.000 < 0.05 means that the chemical equilibrium teaching materials are based on Spiritual values that have been validated by expert validators can develop students' spiritual attitudes. Apart from that, there is also a relationship between students' spiritual attitudes and the learning outcomes of students who are taught using chemical equilibrium teaching materials based on spiritual values in the guided inquiry learning model where the sig value (2-tailed) < 0.05 or 0.024 < 0.05.